Draft Annual Plan 2011-12 Executive Summary Government of Nagaland - Planning Commission (Planning Commission, 2011)
When India gained independence, Nagaland as a State was not in existence. A portion, consisting of the present day Kohima, Dimapur and Mokokchung districts had been brought under British Administration but the rest of the areas were left unadministered. After India's independence, the Naga inhabited areas was divided between India and the then Burma along the watershed and administrative outposts were established in the areas that had remained unadministered under the British. Even then, the Tuensang and Mon areas remained under NEFA (North East Frontier Agency) and not as part of the Naga Hills district that was under Assam. It was after a violent insurgency movement during the fifties that the erstwhile Naga Hills district of Assam and the Tuensang Frontier Division of NEFA, was brought together and formed into a separate administrative unit named as Naga Hill Tuensang Area (NHTA) in 1957 which finally was granted Statehood on Ist December 1963.
Planning & Co-Ordination Department Nagaland, Kohima